2011
DOI: 10.1111/j.1439-0396.2010.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a skullcap root supplement on haematology, serum parameters and antioxidant enzymes in rabbits on a high-cholesterol diet

Abstract: We studied the effects of Scutellaria baicalensis root on blood parameters and antioxidant enzyme activities in rabbits fed a high-cholesterol diet. Thirty-two New Zealand White rabbits were divided into four groups of eight animals each. They were fed a standard diet (C group), a diet with a 1% pure cholesterol supplement (CH group), a diet with a 1% pure cholesterol supplement and a 9% skullcap root supplement (CH+SR group), or a diet with a 9% skullcap root supplement (SR group). After 6 weeks, the rabbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…Another study administered SB to type 2 diabetic db/db mice for four weeks and showed marked improvement in insulin resistance and hypertriglyceridemia [ 26 ]. An experiment with hypercholesterolemic rabbits found that administration of SB lowers plasma total cholesterol and LDL-cholesterol [ 27 ]. This indicates that although metformin did not significantly lower cholesterol, a combination treatment with SB seems to produce an additional effect without interfering with the pharmaceutical efficacy of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Another study administered SB to type 2 diabetic db/db mice for four weeks and showed marked improvement in insulin resistance and hypertriglyceridemia [ 26 ]. An experiment with hypercholesterolemic rabbits found that administration of SB lowers plasma total cholesterol and LDL-cholesterol [ 27 ]. This indicates that although metformin did not significantly lower cholesterol, a combination treatment with SB seems to produce an additional effect without interfering with the pharmaceutical efficacy of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…However, since plant-based phenolic compounds also play both beneficial and detrimental roles in animal nutrition (in particular protein bioavailability), their measurement is important and has not yet been reported for most of the species studied here. Specific phenolic compounds such as terrestrial plant-derived tannins have been shown to provide beneficial effects by inhibiting harmful bacterial colonization of the intestine, as demonstrated in terrestrial livestock such as poultry (Jamroz et al 2003), swine (Van Parys et al 2010), and rabbits (Króliczewska et al 2011). However, this has yet to be demonstrated in farmed animals and fish fed algae-derived phenolic sources.…”
Section: −1mentioning
confidence: 98%
“…Housing requirements can be readily met for rabbits. The rabbits were housed in a room with a proper air flow and maintained at a temperature of 18 ± 1 °C, relative humidity of 55 ± 10% and under lighting cycles (lights on at 07:00) throughout the adaptation period and study . After the adaptation period, the rabbits were randomly divided into three groups of eight animals each.…”
Section: Methodsmentioning
confidence: 99%